2012
DOI: 10.1155/2012/790281
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Stability Analyses by Means of Protein Energy Profiles in Case of Nephrogenic Diabetes Insipidus

Abstract: Diabetes insipidus (DI) is a rare endocrine, inheritable disorder with low incidences in an estimated one per 25,000–30,000 live births. This disease is characterized by polyuria and compensatory polydypsia. The diverse underlying causes of DI can be central defects, in which no functional arginine vasopressin (AVP) is released from the pituitary or can be a result of defects in the kidney (nephrogenic DI, NDI). NDI is a disorder in which patients are unable to concentrate their urine despite the presence of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…For more information, please refer to the discussions in references [7,4,9]. The underlying coarse-grained energy model applied by eProS services utilizes concepts of statistical physics.…”
Section: Theoretical Background: Energy Model and Energy Profile Predmentioning
confidence: 99%
See 3 more Smart Citations
“…For more information, please refer to the discussions in references [7,4,9]. The underlying coarse-grained energy model applied by eProS services utilizes concepts of statistical physics.…”
Section: Theoretical Background: Energy Model and Energy Profile Predmentioning
confidence: 99%
“…Recent studies have demonstrated that sequences of energy values, referred to as energy profiles, obtained from protein structures using fine and coarse-grained energy models can be used to characterize protein functionality and structural features [10,11,7,9]. Mrozek et al had introduced a dynamic programming approach for generating energy profile alignments [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses of proteins based on energy profiles can contribute in understanding correspondences of protein sequence to structure, stability and function (7,10,11,21). However, the generation of large scale databases of energy profiles derived from physics-based approaches is difficult to automatize, error-prone and slow.…”
Section: Resultsmentioning
confidence: 99%